From profit to purpose: Sustainability and corporate strategy insights from Desa Inspirasi Padi - Ayu, Kilau Riksaning; Ulya, Himmatul; Nuryanti, Nuryanti (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
The transition to post-modern CSR era marks an evolution towards a more inclusive and holistic understanding of corporate social responsibility, extending beyond mere economic gains to address broader social aspects like food security. This study examines the Desa Inspirasi Padi program by Sido Muncul Pupuk Nusantara through the Triple Bottom Line (3P: People, Planet, Profit) framework and a post-modern perspective, aiming to understand how CSR can integrate with food security issues. A qualitative method is employed to explore the implementation and impact of the program, revealing the importance of a holistic and context-sensitive approach. Findings indicate that collaboration between corporations, government, and local communities is crucial in addressing social and environmental challenges. Despite financial constraints, this study highlights the significance of stakeholder support and strategic partnerships for sustainable impact. This research contributes insights into the role of CSR in navigating complex socio-environmental landscapes, offering a fresh perspective for CSR practices in the post-modern era.